2023
DOI: 10.1002/smtd.202201381
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Immunotherapy Elicited by Immunogenic Cell Death Based on Smart Nanomaterials

Abstract: Cancer immunotherapy has been a revolutionary cancer treatment modality because it can not only eliminate primary tumors but also prevent metastases and recurrent tumors. Immunogenic cell death (ICD) induced by various treatment modalities, including chemotherapy, phototherapy, and radiotherapy, converts dead cancer cells into therapeutic vaccines, eliciting a systemic antigen‐specific antitumor. However, the outcome effect of cancer immunotherapy induced by ICD has been limited due to the low accumulation eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 180 publications
0
9
0
Order By: Relevance
“…For the past few years, photodynamic therapy (PDT) has become a promising treatment for solid tumors. , Under a specific wavelength of laser radiation, PDT molecules would generate reactive oxygen species (ROS) in the presence of sufficient oxygen to induce the chemical damage of tumor cells. In addition, PDT also initiates antitumor immunity by promoting antigen presentation to cytotoxic T lymphocytes to reverse the immunosuppressive microenvironment. , Due to its merits like small trauma, low side effects, and and high efficiency, PDT is expected to become an efficient therapy method to cure cancer shortly to make up for the limitations of traditional highly poisonous cancer treatments like chemotherapy, radiotherapy, and adoptive cell therapy. …”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, photodynamic therapy (PDT) has become a promising treatment for solid tumors. , Under a specific wavelength of laser radiation, PDT molecules would generate reactive oxygen species (ROS) in the presence of sufficient oxygen to induce the chemical damage of tumor cells. In addition, PDT also initiates antitumor immunity by promoting antigen presentation to cytotoxic T lymphocytes to reverse the immunosuppressive microenvironment. , Due to its merits like small trauma, low side effects, and and high efficiency, PDT is expected to become an efficient therapy method to cure cancer shortly to make up for the limitations of traditional highly poisonous cancer treatments like chemotherapy, radiotherapy, and adoptive cell therapy. …”
Section: Introductionmentioning
confidence: 99%
“…Cancer immunotherapy is an emerging therapeutic approach that harnesses the patient’s own immune system to eliminate tumors via utilizing immune checkpoint blockade antibodies, immune agonists, and vaccines. The combination of immunotherapy and chemotherapy has provided an efficient intervention strategy for postoperative cancer treatment. ,, Recent studies have demonstrated that chemotherapeutics such as doxorubicin and oxaliplatin could induce immunogenic cell death (ICD) of tumor cells to promote systemic antitumor immunity. The ICD effect of tumor cells can facilitate the recruitment and maturation of dendritic cells (DCs) in the tumor microenvironment to boost the antigen presentation. , Intriguingly, intracellular reactive oxygen species (ROS) play a crucial role in activating the hazardous signaling pathway to augment the ICD effect. , The excessive accumulation of ROS in cancer cells above the toxicity threshold can overwhelm the antioxidant system and trigger endoplasmic reticulum (ER) stress, thereof initiating distinct tumor immunogenic cell death. As a typical immunogenic chemotherapeutic drug, DOX generates a significant amount of intracellular ROS to stimulate ICD-related danger signaling via nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4) activation and thioredoxin reductase (TrxR) inhibition, as well as collateral ER stress, thus stimulating the host’s antitumor immune response. As another substance for promoting intracellular ROS levels, curcumin (CUR) can destroy the redox balance in cancer cells by targeting the ROS metabolic enzyme TrxR. Accordingly, the combination of DOX and CUR indicates a potential strategy to amplify ROS generation in cancer cells for converting nonimmunogenic tumors to immunogenic ones that promote DC maturation for chemo-immunotherapy. , However, it remains a significant challenge to cooperatively implement the ICD-inducing and chemotherapeutic features of DOX and CUR for postoperative immunogenic chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Cancer originates from disorderly malignant proliferation caused by mutations in cellular genetic material. 2 Cancer is a serious disease that has a significant impact on human life and health. The disease features over-proliferation signaling, cell death resistance, escape of growth inhibitory factors, activation of angiogenesis, invasive activity and migration.…”
Section: Introductionmentioning
confidence: 99%